2001
DOI: 10.1111/j.2042-7158.2001.tb01796.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of serum angiotensin-converting enzyme in rabbits after intravenous administration of enalaprilat-loaded intact erythrocytes

Abstract: Encapsulation of drugs in intact erythrocytes, because of the profound characteristics of these natural microspheres, has gained considerable attention in recent years. In this study, the inhibition time courses of serum angiotensin-converting enzyme (ACE) activity after intravenous administration of enalaprilat encapsulated in intact erythrocytes was evaluated and compared with free drug, in a rabbit model. Three groups of animals each received free drug, drug-loaded erythrocytes or sham-encapsulated erythroc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…While in plasma it reaches only 72% after 23 hours. These results are comparable to results reported on similar polar drugs including gentamicin38, enalaprilat 39 and heparin 40. Hemoglobin release kinetics is belonged to zero order pattern while pravastatin is belonged to first order kinetics in both two phases.…”
Section: Resultssupporting
confidence: 87%
“…While in plasma it reaches only 72% after 23 hours. These results are comparable to results reported on similar polar drugs including gentamicin38, enalaprilat 39 and heparin 40. Hemoglobin release kinetics is belonged to zero order pattern while pravastatin is belonged to first order kinetics in both two phases.…”
Section: Resultssupporting
confidence: 87%
“…Several studies reported the effect of drugs on fragility behavior of erythrocytes. Hamidi and his workers stated that osmotic fragility of loaded erythrocytes is lower than unloaded cells 23 . On contrast, another study revealed that osmotic fragility of carrier erythrocytes is higher than unloaded cells 24 .…”
Section: Osmotic Fragility Behavior Of Salbutamol Loaded Erythrocytesmentioning
confidence: 99%
“…As an advantage, in the optimum conditions of the loading procedure (using more gentle methods for loading), the life‐span of the resulting carrier cells may be comparable with that of normal erythrocytes [1,6,7] . Erythrocytes have been used as circulating intravenous slow‐release carriers for the delivery of antineoplasm agents, antiparasitic drugs, antiretroviral agents, vitamins, steroids, antibiotics, and cardiovascular drugs among others [1,6–34] …”
Section: Introductionmentioning
confidence: 99%